Reading comprehension difficulties in people with aphasia: investigating personal perception of reading ability, practice, and difficulties. Issue 6 (3rd June 2021) - Webster, Janet; Morris, Julie; Malone, Jenny; Howard, David
ABSTRACT: Background : Whilst reading difficulties are a common feature of aphasia, there has been limited consideration of the impact of these difficulties on how people with aphasia experience reading in their everyday lives. Previous studies, using semi-structured interviews, have highlighted the need to consider reading from the perspective of the individual due to the complexity of factors influencing reading and individual variation in practices and preferences. These studies have contributed to our understanding of the individual's perspective but have been restricted to people with less severe aphasia and some expressive ability. We need tools to facilitate understanding the personal perspective of people across the severity range that are feasible within a clinical setting. Aims : The aim of this study was to investigate people with aphasia's perception of their current reading ability and activities and feelings about reading using a questionnaire. The validity, reliability, and clinical usefulness and acceptability of the questionnaire were considered. Methods & Procedures : The questionnaire was developed through an iterative process, involving a review of literature, integration of findings from an interview study, direct consultation with people with aphasia, pilot testing, and review. The questionnaire comprised four sections: A) Current reading, B) Thoughts and feelings about reading, C) Reading activities, and D) Reading strategies. Eighty-one participants completed the questionnaire during a study of reading in people with aphasia. Following completion of data collection, tester feedback was considered and the psychometric properties of the questionnaire in relation to aspects of validity and reliability were analysed. Outcomes & Results : Perception of reading ability, feelings about reading and reading activity varied considerably across participants, with not all individuals reporting difficulties. There was increased perceived difficulty as the length of text increased. Participants highlighted that they were unhappy with their speed of reading. The most common strategies used to support reading were re-reading, slowing down, and reducing distractions. The iterative process resulted in a 29 item questionnaire which had appropriate face validity, construct validity and test re-test reliability and was clinically appropriate and feasible. Conclusions : The study provides additional evidence about the individual variability in reading in people with aphasia, emphasising the importance of considering personal perception alongside formal assessments of reading comprehension. The questionnaire provides a practical and reliable measure of a person's perception of reading post-stroke and has potential as a patient-centred tool, contributing to goal setting and outcome measurement.